2020
DOI: 10.1261/rna.076117.120
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionarily conserved RNA structure in the functional core of the lincRNA Cyrano

Abstract: The wide prevalence and regulated expression of long noncoding RNAs (lncRNAs) highlight their functional roles, but the molecular basis for their activities and structure-function relationships remains to be investigated, with few exceptions. Among the relatively few lncRNAs conserved over significant evolutionary distances is the long intergenic noncoding RNA (lincRNA) Cyrano (orthologous to human OIP5-AS1), which contains a region of 300 highly conserved nucleotides within tetrapods, which in turn contains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 79 publications
1
29
0
Order By: Relevance
“…Nevertheless, a recent report revealed that there was a highly conserved 300-nucleotide fragment within the long exon 3 of Cyrano that contained miR-7-binding sites and maintained a similar cloverleaf secondary structure in most species. 43 Knocking out this conserved section of exon 3 in mice showed miR-7 upregulation in brain tissue. 37 Moreover, two independent groups recently reported that the ZSWIM8 Cullin-RING ligase mediates miR-7 degradation caused by Cyrano in a human cell line, 44,45 which indicates that Cyrano/ miR-7 regulation exists in multiple cellular contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a recent report revealed that there was a highly conserved 300-nucleotide fragment within the long exon 3 of Cyrano that contained miR-7-binding sites and maintained a similar cloverleaf secondary structure in most species. 43 Knocking out this conserved section of exon 3 in mice showed miR-7 upregulation in brain tissue. 37 Moreover, two independent groups recently reported that the ZSWIM8 Cullin-RING ligase mediates miR-7 degradation caused by Cyrano in a human cell line, 44,45 which indicates that Cyrano/ miR-7 regulation exists in multiple cellular contexts.…”
Section: Discussionmentioning
confidence: 99%
“…These inconsistencies from different groups might be due to the genetic tools used or species differences. Nevertheless, a recent report revealed that there was a highly conserved 300‐nucleotide fragment within the long exon 3 of Cyrano that contained miR‐7 ‐binding sites and maintained a similar cloverleaf secondary structure in most species 43 . Knocking out this conserved section of exon 3 in mice showed miR‐7 upregulation in brain tissue 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the secondary structure conservation of lncRNAs is lower than that of messenger RNAs or ribosomal RNAs [ 20 , 59 ], some functional lncRNAs with experimentally confirmed structural motifs, including Cyrano [ 60 ], Xist [ 61 , 62 ], MALAT1 [ 63 , 64 ], SRA [ 65 ] and GAS5 [ 66 ], have been found. For instance, recently published studies on MALAT1 in vertebrates revealed an evolutionarily conserved core consisting of numerous helices [ 64 ].…”
Section: Secondary Structure Conservationmentioning
confidence: 99%
“…For instance, recently published studies on MALAT1 in vertebrates revealed an evolutionarily conserved core consisting of numerous helices [ 64 ]. At the center of the functional core of Cyrano is a cloverleaf structure maintained for more than 400 million years, enriched in several protein binding sites and masking a target site for miR-7 [ 60 ]. The aforementioned studies were based on a similar approach: secondary structures are experimentally determined by chemical and/or enzymatic probing and then used in comparative sequence analyses.…”
Section: Secondary Structure Conservationmentioning
confidence: 99%
“…2B). [52][53][54][55][56][57] This was performed in the LNCaP prostate cancer cell line, which is derived from supraclavicular lymph nodes, 58 has high SChLAP1 expression, 15 and a known metastatic phenotype. Multiple aspects of the minimum free energy (MFE) structure are consistent in cellulo as in vitro, namely the 4WJ, large loop structure, and extended stem loop structure.…”
Section: Identification Of In Vitro Structure and Protein-binding Sites Within Schlap1 By Shape-mapmentioning
confidence: 99%